ASSESSING VULNERABILITY TO EXTREME RAINFALL EVENTS IN THE NORTH-EASTERN PART OF CENTRAL JAVA - , Fitria Nucifera, Dr. M.Pramono Hadi, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Extreme rainfall event naturally occurs in the climate system. However, in the last decade frequency and intensity of extreme rainfall events has been increased. Extreme rainfall events frequently triggered some disasters such as flood and landslide. Most of extreme events occurred in the last decade in Indonesia are wet extreme events. Hence, this research will be focused on wet extreme events. North-eastern part of Central Java frequently suffers flooding due to extreme rainfall events. It is important to assess the vulnerability to rainfall extreme events in this area. The objectives of this research are: 1) to identify spatial and temporal distribution of extreme rainfall events